Domestic Crime from a Legal and Societal Perspective - Muhammad Aditya; Riska Ramadhani; Zalfa Azzahra; Yuspita Syawaliah; Najwa Najwa; Afi Kamilia (Jurnal Litigasi Amsir, 2025)
This study examines sexual violence perpetrated by stepparents against children under their care as a form of failure of the child protection system within the family. It focuses on the dynamics of remarriage families, which often create power imbalances, making stepchildren, especially girls, highly vulnerable to violence. Using a normative and empirical approach, this study analyzes Undang Undang Nomor 35 Tahun 2014 tentang Perlindungan Anak and Undang Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual, and combines these with interview results and case studies in Parepare, South Sulawesi. The results indicate that sexual violence in stepfamilies is triggered by weak social control, the mother's economic dependence on her new husband, as well as a closed legal process and minimal victim recovery services. Therefore, integrated steps are needed, including legal reform, strengthening child protection institutions, and changing social culture so that every child is protected in a real, dignified, and just manner